Implementación de un sistema de costos para la asociación de confeccionistas de Cotopaxi "ASOCONFEC", ubicado en la ciudad de Latacunga. - Ayala Unaucho, Byron Patricio (2020)
A significant amount of companies need to know the cost of each of their products to make countless decisions; however, they only see an approximation of those costs since they have an inadequate or non-existent cost system. Therefore, it is essential that a cost system was developed for the "Asociación de confeccionistas de Cotopaxi" to correct the poor control of the accounting records, especially the determination of the cost elements. The objective of this integrative project is to create a system that adapts to the production needs to guarantee efficient management and economic control, avoiding waste of material and technological resources. The information was collected through techniques such as the interview and the observation guide made to the principal of the association and the workers. Through the situational diagnosis, a clearer idea of the problem in question was obtained. Also, the competences related to the professional field and the technical-scientific foundation are described, which contributed to the achievement of this application work. The result of the project generated a cost of sale for school uniforms of size 4 of $ 18.75 while in size 8 is $ 20.98. It was also determined that the current price obtained in the sale of school kits is higher than the calculations obtained through the cost system, adding a profit margin of 10%. The highest percentage of costs incurred in the preparation of sizes 4 and 8 of school uniforms is the raw material, with more than 80% of the total elements. The Association is recommended to apply the cost system for production orders, which allows establishing the real value of the elements of the cost involved in the preparation of school kits; also, to take into account the depreciation of the machinery and the materials that must be bought wholesale to reduce costs